Optimalisasi Pembelajaran Daring Melalui Program Psikoedukasi dan Pendampingan Pembelajaran Digital di TK Ekasari Kabupaten Temanggung - Savara Salsabila; Elysa Diana Puspitasari; Putri Uswatun Khasanah; Dewi Agus Cahyani; Dani Dani; Aning Az Zahra (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The purpose of this activity is to assist the teaching and learning process at Ekasari Kindergarten with digital learning methods. This learning process needs to be carried out because of the determination of distance learning policies due to the covid 19 pandemic. The method or stage of service is by providing assistance and also psychoeducation which is carried out for approximately 1 month to solve the partner's problems. The work programs carried out are non-training psychoeducation, making learning journals, helping the teaching and learning process to students, providing assistance to teachers and guardians of students regarding the use of digital media in the learning process, and psychoeducation which is carried out directly by lecturers as well as parenting students' parents. The result of this activity is that the understanding of partners regarding digital learning has increased and helps the current teaching and learning process, so that it can maximize learning and also the material that will be delivered to students. In addition, this understanding of digital learning can be useful for the sustainability of education in subsequent schools.